The Way to Design Web-based (EMP) Course in EFL Context: A Bridge from Evaluation to Course Design - Abubaker Faraj, Basim M.; Mohamed, Ghada (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
As the worldwide use of English increases it has become indispensable in educational, vocational and professional environments. As a result, English for specific purposes (ESP) has a central role in teaching English at the tertiary level. With rapid advances in technological development, technology has emerged as one of the key aspects of teaching and learning English in classrooms. Based on the students’ needs to use technology in learning English for medical purposes (EMP), the internet has turned into a valuable EMP resource. However, the selection of appropriate websites that match the learners’ and teachers’ needs can turn into a time-consuming process.